Implications of Green Practices in the Hotel Industry: A Study in Jaffna District - Kajotha, V.; Sangarathas, T.; Dilogini, S. (University of Jaffna, 2016)
This study aims at implication of green practices in current hotel industry in the Jaffna district and perception of industries regarding green practices in hotel management in Jaffna. It is well known that the environment is an important resource for the hotel industry, and so the acquisition and application of new technologies that contribute to environmental protection. In some sectors of the hotel industry green aspect has been a priority for hoteliers and as well as customers of accommodation structures. Researchers led a qualitative approach by running in-depth interview method by using open ended questions with the manager of Tilko hotel and Green grass hotel in Jaffna. The results showed that the main reason why hotels become green is because of the pressure the stakeholders and rules and regulations of Government. More over this research identifies what are the green practices that are taken by the hotel Tilko and Green grass in Jaffna, and what are the practices have to be taken in Jaffna. The main steps hotels followed to achieve this objective is not easy; hotels have to spend big cost associated to become green. At the end of the study, some suggestions will be given to hoteliers as well as some suggestion for future researchers.
Keywords: Energy usage; Green hotel; Water usage; Waste management